Duodenal varices as an unusual cause of gastrointestinal bleeding due to portal hypertension: A case report - Haldun SELÇUK; Fatih BOYVAT; Serdar EREN; Murat KORKMAZ; Gürden GÜR; Uğur YILMAZ; Sedat BOYACIOĞLU (Turkish Journal of Gastroenterology, 2019)
-